2018
DOI: 10.1007/s11356-018-2130-z
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of carbendazim in water via photo-Fenton in Raceway Pond Reactor: assessment of acute toxicity and transformation products

Abstract: This study aimed at investigating the degradation of fungicide carbendazim (CBZ) via photo-Fenton reactions in artificially and solar irradiated photoreactors at laboratory scale and in a semi-pilot scale Raceway Pond Reactor (RPR), respectively. Acute toxicity was monitored by assessing the sensibility of bioluminescent bacteria (Aliivibrio fischeri) to samples taken during reactions. In addition, by-products formed during solar photo-Fenton were identified by liquid chromatography coupled to mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 36 publications
5
13
0
Order By: Relevance
“…As confirmed by the results shown in Figure 3, CBZ is known to be toxic to Allivibrio fischeri [80]. Similarly to what was observed for CAF, UV-C photolysis alone was not able to remove CBZ due to its low molar absorptivity and quantum yield.…”
Section: Evolution Of Acute Toxicitysupporting
confidence: 68%
See 2 more Smart Citations
“…As confirmed by the results shown in Figure 3, CBZ is known to be toxic to Allivibrio fischeri [80]. Similarly to what was observed for CAF, UV-C photolysis alone was not able to remove CBZ due to its low molar absorptivity and quantum yield.…”
Section: Evolution Of Acute Toxicitysupporting
confidence: 68%
“…Consequently, UV-C photolysis had a negligible effect on the acute toxicity of CBZ. Meanwhile, both UV-C/H2O2 and UV-C/S2O8 2eliminated the toxic effect of CBZ; as it was also observed by other irradiated AOPs under artificial and solar irradiation in another study [80]. During UV-C/H2O2, CBZ degradation occurred alongside the reduction in acute toxicity (Figure 3).…”
Section: Evolution Of Acute Toxicitysupporting
confidence: 54%
See 1 more Smart Citation
“…For example, da Costa et al [72] found a similar value for a.T.U. toxicity for their nontreated CBZ water solution and the authors observed an increase of toxicity for UV photolysis and UV-H2O2 processes, due to the by-products formed.…”
Section: (A) (B)mentioning
confidence: 77%
“…Although the toxic effect of carbendazim has been reported since the 1980s, the toxicity of carbendazim becomes a hot topic because of the increasing concern about environmental endocrine disruptors [4]. Carbendazim has been banned in several countries because of its negative impacts on the environment and health such as development and reproductive disturbances, toxicity, and mutagenicity [8].…”
Section: Introductionmentioning
confidence: 99%